ПОЛІПШЕННЯ ФІЗИКО-МЕХАНІЧНИХ ХАРАКТЕРИСТИК СИНТЕТИЧНИХ АЛМАЗІВ ДЛЯ ПРАВЛЯЧОГО ІНСТРУМЕНТУ - Пріхна, Тетяна Олексіївна; Ільницька, Галина Дмитрівна; Лавріненко, Валерій Іванович; Логінова, Ольга Борисівна; Гаращенко, Віктор Володимирович; Соколов, Олександр Миколайович; Зайцева, Ірина Миколаївна; Смоквина, Володимир Віталійович; Косенчук, Тамара Олександрівна (Институт сверхтвердых материалов им. В. Н. Бакуля Национальной академии наук Украины, 2020)
The results of studies of the influence of heat treatment on the physicomechanical characteristics of 500/400 and 250/200 grit diamond grinding powders after their separation in a magnetic field of different strengths are presented. It is shown that for both grit sizes, separation in a magnetic field facilitates the production of diamond fractions that differ in the content of intracrystalline inclusions in them and the change in their physical and mechanical characteristics: strength, uniformity in strength, and heat resistance. In diamond powders with a higher content of intracrystalline inclusions, after heat treatment in an inert medium, a decrease in the strength of crystals is observed for both grit sizes both at a temperature of 800 °C and at 1100 °C. In diamond powders with a lower content of intracrystalline inclusions after processing at a temperature of 800 °C, due to a decrease in internal stresses, an insignificant (not more than 5 %) increase in strength occurs. The thermal stability of both grit sizes for all studied diamond fractions, decreases with an increase in the content of intracrystalline inclusions in them